Pendekatan Latihan Pernapasan: Studi Kasus Tunggal Disfonia pada Pasien 43 Tahun - Jumiarti; Stefany Putri Mardatila (Politeknik Arutala Johana Hendarto [d.h. Akademi Terapi Wicara], 2025)
Background: Voice problems are very common among teacher, including those in special school. The characteristic of a hoarseness and weal voice can significantly impact a person’s daily activities. Voice therapy conducted by speech therapist aims to optimize vocal function in order to improve the patient’s quality of life Objectives: The purpose of this study is to obtain on overview of subjective voice changes during the dysphonia treatment process in special school teachers. Methods: This research uses a qualitative approach with a pre-post test experimental design, employing single subject research. The case study focuses on voice improvement efforts through two phases: assessment and intervention. The participant is a 43-year-old female teacher at a special school who experiences hoarseness with a history of chronic severe anemia. Breathing exercises intervention was given with a total of ten sessions using the Respiration Training method. Acoustic, aerodynamic, and auditory perceptual voice quality measurements were taken before therapy. Maximum Phonation Time (MPT) measurement was conducted before aand after therapy. Result: Comparing the Maximum Phonation Time results before and after voice therapy shows an increased duration ability by lengthening the vowel. Conclusion: Breathing exercises can help clients control airflow and subglottic pressure by prolonging Maximum Phonation Time and improving voice efficiency. Breathing exercises can be combined with other phonation techiques to further enhance voice strength and more efficient phonation.